2022
DOI: 10.1002/jrsm.1547
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of prevalence: I2 statistic and how to deal with heterogeneity

Abstract: Over the last decade, there has been a 10‐fold increase in the number of published systematic reviews of prevalence. In meta‐analyses of prevalence, the summary estimate represents an average prevalence from included studies. This estimate is truly informative only if there is no substantial heterogeneity among the different contexts being pooled. In systematic reviews, heterogeneity is usually explored with I‐squared statistic (I2), but this statistic does not directly inform us about the distribution of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(128 citation statements)
references
References 19 publications
2
125
0
1
Order By: Relevance
“…When interpreting the results, we distinguished between the average summary SMD from the meta-analysis and the expected SMDs shown in the range of the PrI. We estimated between-study heterogeneity by considering the SD of the random effects (τ) and the width of the PrI rather than the I 2 metric ( 18 , 19 ). To enhance interpretation, we transformed summary SMDs into mean differences on the Patient Health Questionnaire-9 scale for depression and on the General Anxiety Disorder-7 scale for anxiety, using the observed pooled SDs of a large representative study ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…When interpreting the results, we distinguished between the average summary SMD from the meta-analysis and the expected SMDs shown in the range of the PrI. We estimated between-study heterogeneity by considering the SD of the random effects (τ) and the width of the PrI rather than the I 2 metric ( 18 , 19 ). To enhance interpretation, we transformed summary SMDs into mean differences on the Patient Health Questionnaire-9 scale for depression and on the General Anxiety Disorder-7 scale for anxiety, using the observed pooled SDs of a large representative study ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the pathogens with at least five studies, heterogeneity was greater than 75%. This is expected with a meta-analysis of prevalence studies because of the difference in the sampling frame, sampling technique, sampling size, diagnostic tool, and differing biomarkers reported as a result [26] .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, studies indicated that a high I 2 value is not always synonymous with high heterogeneity, and, like this study, when only a small number of studies with no true heterogeneity are included in the meta‐analysis, I 2 will overestimate heterogeneity. 37 , 38 It could not be therefore difficult to utilize this paper for different purposes. The publication bias has also been overcome by conducting trim and fill analysis.…”
Section: Discussionmentioning
confidence: 99%